2014
DOI: 10.1136/jnnp-2014-307654
|View full text |Cite
|
Sign up to set email alerts
|

Female gender doubles executive dysfunction risk in ALS: a case-control study in 165 patients

Abstract: Results highlight a significant vulnerability of ALS female patients to develop cognitive dysfunctions peculiar to the disease, independently of bulbar onset. The explicative hypotheses of the data are focused on two interpretative lines not mutually exclusive: the role of gonadal hormones and gender-related brain asymmetry pre-existing to the disease. These findings, never reported before in the literature, can have important implications for models of ALS pathogenesis and for future clinical trial designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Even though some studies have used the CPM as an indicator for visuospatial dysfunctions and found impairment in only very few cases [22], ALS patients performed worse in the CPM than HC in this study. This is also in accordance with other studies using this test as a tool for non-verbal executive reasoning in ALS patients [21]. The main advantage of the CPM seems to be its robustness among different approaches of application, as a strong correlation between performance in the motor and motorfree variants could be observed in both groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Even though some studies have used the CPM as an indicator for visuospatial dysfunctions and found impairment in only very few cases [22], ALS patients performed worse in the CPM than HC in this study. This is also in accordance with other studies using this test as a tool for non-verbal executive reasoning in ALS patients [21]. The main advantage of the CPM seems to be its robustness among different approaches of application, as a strong correlation between performance in the motor and motorfree variants could be observed in both groups.…”
Section: Discussionsupporting
confidence: 87%
“…The CPM is a non-verbal test of fluid intelligence, visuospatial reasoning and executive functioning whose paper-pencil version has shown to be effective in revealing cognitive deficits among non-demented ALS patients [21,22]. The D2-test is a non-verbal test for executive dysfunction in the domains of selective and sustained attention and visual processing speed.…”
Section: Introductionmentioning
confidence: 99%
“…We anticipated that education level would be correlated with the total ECAS score. However, gender [ 35 ] and age [ 25 ] were also thought to be important influential factors. One explanation might be that some other variants affect cognitive function, such as occupation and social economic status.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature on this field remains scarce, especially about the role of gender in the risk of developing specific cognitive impairment in ALS. Palmieri et al [ 73 ] tried to identify specific gender-related differences in cognitive profile in ALS through a retrospective study in a representative cohort of Italian outpatients with ALS. Independent from mood tone and clinical variables, a significantly greater executive impairment was found in female patients compared to males and control participants.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%